Positive electrode active material precursor, its manufacturing method, positive electrode active material, and manufacturing method of positive electrode active material
Patent Information
- Application Number
- JP2024543359
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2043-08-17
AI Technical Summary
【0036】 本発明による正極活物質前駆体は、一次粒子が薄く、二次粒子が緻密であることから、粒子の内部コア部は空隙が多く、外部シェルは緻密で微細空隙が均一に分布されており、定義する面積の比および空隙率を有することができ、これにより、前記正極活物質前駆体を適用した正極活物質の充放電容量性能を改善することができる。
Smart Images

Figure 2025505379000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0102627 filed on August 17, 2022 and Korean Patent Application No. 10-2022-0125537 filed on September 30, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated by reference into this specification.
[0002] The present invention relates to a positive electrode active material precursor, a method for producing the same, a positive electrode active material, and a method for producing a positive electrode active material using the same. [Background technology]
[0003] As technology for mobile devices develops and demand increases, the demand for secondary batteries as an energy source is rapidly increasing. Among these secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0004] Lithium transition metal composite oxides are used as the positive electrode active material for lithium secondary batteries, and among them, the lithium cobalt composite metal oxide LiCoO2, which has a high working voltage and excellent capacity characteristics, is mainly used. However, LiCoO2 has very poor thermal properties due to the instability of its crystal structure caused by delithiation, and it is expensive, so there are limitations to its mass use as a power source in fields such as electric vehicles.
[0005] Materials that have been developed to replace LiCoO2 include lithium manganese composite metal oxides (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), and lithium nickel composite metal oxides (LiNiO2, etc.). Among these, active research and development has been conducted on lithium nickel composite metal oxides, which have a high reversible capacity of approximately 200 mAh / g and can easily be used to create large-capacity batteries. However, LiNiO2 has inferior thermal stability compared to LiCoO2, and if an internal short circuit occurs due to external pressure while the battery is charged, the positive electrode active material itself decomposes, causing the battery to explode and catch fire.
[0006] Therefore, nickel-cobalt-manganese-based lithium composite metal oxides (hereinafter simply referred to as "NCM-based lithium oxides") have been developed in which part of the Ni is replaced with Mn and Co, as a way to maintain the excellent reversible capacity of LiNiO2 while improving its low thermal stability.
[0007] However, due to the recent increase in the price of cobalt (Co), lithium-rich NCM-based positive electrode active materials that contain a relatively small amount of cobalt (Co) and can meet high capacity requirements are being developed.
[0008] In general, the precursor of NCM-based positive electrode active material is synthesized by coprecipitation, where ammonia (NH4OH) is used as a complexing agent, which is a necessary raw material. Ammonia forms a complex with a metal salt during the synthesis of the precursor, and acts as a catalyst to facilitate the synthesis of the precursor. Ammonia is an essential raw material for the synthesis of the precursor, but it has a bad odor and is an environmentally regulated substance, which increases the production cost of the precursor.
[0009] In addition, ammonia acts as a catalyst and has a significant effect on the physical properties of the precursor, such as particle size and particle morphology, depending on the concentration (amount) of ammonia. Therefore, in order to produce a positive electrode active material with high physical property reproducibility, the physical property reproducibility of the positive electrode active material precursor must be high, and therefore, the amount of ammonia used, which affects this, must be precisely controlled, which is inconvenient for the process.
[0010] Therefore, there is a need for the development of a method for producing a positive electrode active material precursor that can smoothly carry out a coprecipitation reaction even in the absence of ammonia, is environmentally friendly, has high process efficiency, and has excellent reproducibility of physical properties. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Korean Patent Publication No. 10-2016-0063982 (Publication date: June 7, 2016) Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made to solve the above problems, and has an object to provide a positive electrode active material precursor having excellent particle strength.
[0013] Another object of the present invention is to provide a method for producing the positive electrode active material precursor, which allows the coprecipitation reaction to proceed smoothly even in the absence of ammonia, is environmentally friendly, and has excellent reproducibility of physical properties.
[0014] Another object of the present invention is to provide a positive electrode active material containing a lithium transition metal oxide which is a reaction product of the positive electrode active material precursor and a lithium source material.
[0015] It is another object of the present invention to provide a method for producing a positive electrode active material using the positive electrode active material precursor. [Means for solving the problem]
[0016] In order to solve the above problems, the present invention provides a positive electrode active material precursor, a method for producing the same, a positive electrode active material, and a method for producing a positive electrode active material using the positive electrode active material precursor.
[0017] (1) The present invention provides a positive electrode active material precursor that includes secondary particles formed by agglomeration of a plurality of primary particles, the secondary particles having a ratio of a core area to a total area of the particle (core area / total area) of 28.7% to 34.1% and a porosity represented by the following mathematical formula 1 of 11.3% to 11.7%: [Mathematical formula 1] Porosity (%) = (void area of whole particle / area of whole particle) x 100
[0018] (2) The present invention provides a positive electrode active material precursor according to (1) above, wherein the secondary particles have a core porosity of 13.5% to 15.0%.
[0019] (3) In the present invention, in the above (1) or (2), the average particle diameter of the secondary particles (D 50 ) is 3 μm to 15 μm.
[0020] (4) The present invention provides a positive electrode active material precursor according to any one of the above (1) to (3), wherein the primary particles are acicular with a thickness of 40 nm to 100 nm and an aspect ratio of 3 to 10.
[0021] (5) In any one of the above (1) to (4), the present invention provides a positive electrode active material precursor represented by the following chemical formula 1: [Chemical formula 1] [Ni a Mn b M 1 c ](OH)2 In the above Chemical Formula 1, 0 <a<0.4、0.5≦b<1、0≦c≦0.1であり、M 1 is one or more selected from the group consisting of Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Mo, Y, W and Zr.
[0022] (6) The present invention relates to any one of the above (1) to (5), 2 / g~35m 2 / g and a tap density of 1.4 g / cc to 2.0 g / cc.
[0023] (7) The present invention relates to any one of the above (1) to (5), 2 / g~30m 2 / g and a tap density of 1.4 g / cc to 2.0 g / cc.
[0024] (8) The present invention provides a method for producing a positive electrode active material precursor, comprising the step of producing a reaction solution containing a transition metal hydroxide by co-precipitation reaction of two or more transition metal raw materials in the presence of a basic aqueous solution under a nitrogen atmosphere, wherein the co-precipitation reaction is carried out by introducing air in the absence of ammonia.
[0025] (9) The present invention provides the method for producing a positive electrode active material precursor according to (8) above, wherein the air is introduced in an amount of more than 0 vol % and less than 10 vol % relative to 100 vol % of nitrogen.
[0026] (10) The present invention provides the method for producing a positive electrode active material precursor according to (8) or (9), wherein the co-precipitation reaction is carried out by continuously introducing air, and a total amount of air introduced during the co-precipitation reaction is more than 0 vol % and not more than 5 vol % relative to a total amount of nitrogen used in the co-precipitation reaction (100 vol %).
[0027] (11) The present invention provides the method for producing a positive electrode active material precursor according to any one of the above (8) to (10), further comprising a step of aging the reaction solution, in which the aging is performed by leaving the reaction solution to stand under a nitrogen atmosphere under conditions of a pH of 12 to 14 for 6 hours to 24 hours.
[0028] (12) The present invention provides the method for producing a positive electrode active material precursor according to any one of the above (8) to (11), wherein the aging is carried out in a temperature range of 30°C to 50°C.
[0029] (13) The present invention provides a method for producing a positive electrode active material precursor according to any one of the above items (8) to (12), comprising the steps of: co-precipitating two or more kinds of transition metal source materials in the presence of a basic aqueous solution under a nitrogen atmosphere to produce a reaction solution containing a transition metal hydroxide; aging the reaction solution; and sequentially carrying out washing, filtration, and drying.
[0030] (14) The present invention provides the method for producing a positive electrode active material precursor according to the above (13), wherein the washing comprises primary washing and secondary washing in that order, the primary washing being performed using a basic aqueous solution, and the secondary washing being performed using distilled water.
[0031] (15) The present invention provides the method for producing a positive electrode active material precursor according to any one of (8) to (14) above, wherein the transition metal is two or more selected from Ni, Co, Mn, Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Y, Mo, W, and Zr.
[0032] (16) The present invention provides a cathode active material comprising a lithium transition metal oxide that is a reaction product of a cathode active material precursor according to any one of (1) to (7) above and a lithium raw material, and comprising secondary particles formed by agglomeration of a plurality of primary particles, the secondary particles having a shell thickness ratio to a semi-major axis of the particle of 30% to 60%.
[0033] (17) The present invention provides a positive electrode active material represented by the following chemical formula 2 in the above (16): [Chemical formula 2] Li x [Ni a Mn b M 1 c ]O2 In the above Chemical Formula 2, 1.1 <a<1.3、0<a<0.4、0.5≦b<1、0≦c≦0.1、x+a+b+c=2であり、M 1 is one or more selected from the group consisting of Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Mo, Y, W and Zr.
[0034] (18) The present invention provides a method for producing a positive electrode active material, comprising the steps of mixing the positive electrode active material precursor according to any one of (1) to (7) above with a lithium source material, and calcining the mixture.
[0035] (19) The present invention provides the method for producing a positive electrode active material according to (18), wherein the positive electrode active material precursor and a lithium source material are mixed such that a molar ratio of lithium elements in the positive electrode active material precursor and the lithium source material is 1:1.2 to 1:1.6. Effect of the Invention
[0036] The cathode active material precursor according to the present invention has thin primary particles and dense secondary particles, and therefore the inner core of the particle has many voids and the outer shell is dense with microvoids uniformly distributed, thereby having a defined area ratio and porosity, thereby improving the charge / discharge capacity performance of a cathode active material using the cathode active material precursor.
[0037] In addition, the method for producing a positive electrode active material precursor according to the present invention involves conducting a coprecipitation reaction under a nitrogen atmosphere by introducing air, so that the precursor can be easily produced even in the absence of ammonia, which is environmentally friendly and provides excellent reproducibility of the precursor properties. [Brief description of the drawings]
[0038] The following drawings attached to this specification are intended to illustrate specific embodiments of the present invention and, together with the above-mentioned content of the invention, serve to further understand the technical concept of the present invention. The present invention should not be interpreted as being limited only to the matters depicted in such drawings.
[0039] [Figure 1]FIG. 1 shows SEM analysis results of the positive electrode active material precursor of Example 1, including (a) particle shape at 2K magnification, (b) particle shape at 15K magnification, (c) particle shape at 50K magnification, and (d) particle cross-sectional image at 20K magnification. [Diagram 2] 1 shows SEM analysis results of the positive electrode active material precursor of Comparative Example 1, including (a) particle shape at 2K magnification, (b) particle shape at 15K magnification, (c) particle shape at 50K magnification, and (d) particle cross-sectional image at 20K magnification. [Diagram 3] FIG. 1 shows SEM analysis results of the positive electrode active material precursor of Comparative Example 2, including (a) particle shape at 2K magnification, (b) particle shape at 15K magnification, (c) particle shape at 50K magnification, and (d) particle cross-sectional image at 20K magnification. [Figure 4] 1 shows the results of SEM analysis of the positive electrode active material precursor of Comparative Example 3, including (a) an image of the particle shape at 2K magnification and (b) an image of the particle shape at 15K magnification. [Diagram 5] 1 shows the results of SEM analysis of the positive electrode active material precursor of Comparative Example 4, in which (a) is an image of the particle shape at 2K magnification and (b) is an image of the particle shape at 15K magnification. [Figure 6] 4 is a graph comparing the particle size distributions of the positive electrode active material precursors of Example 1 and Comparative Examples 1 to 4. [Figure 7] 1 shows the results of SEM analysis of the positive electrode active material of Example 1, where (a) is a particle shape at 50K magnification and (b) is a cross-sectional image of a particle at 50K magnification. [Figure 8] 1 shows the results of SEM analysis of the positive electrode active material of Comparative Example 1, where (a) is a particle shape at 50K magnification and (b) is a cross-sectional image of a particle at 50K magnification. [Figure 9] 1 shows the results of SEM analysis of the positive electrode active material of Comparative Example 2, where (a) is an image of a particle shape at 50K magnification and (b) is an image of a particle cross section at 50K magnification. [Figure 10] 1 shows SEM analysis results of the positive electrode active material precursor of Example 2, (a) an image of particle shape at 15K magnification and (b) an image of particle shape at 1K magnification. [Figure 11]1 shows the results of SEM analysis of the positive electrode active material precursor of Example 3, in which (a) is an image of the particle shape at 15K magnification and (b) is an image of the particle shape at 1K magnification. [Figure 12] 1 is an XRD graph of the positive electrode active material precursor of Example 2 and Example 3. [Figure 13] 1 shows SEM analysis results of the positive electrode active material of Example 2, (a) an image of particle shape at 25K magnification and (b) an image of particle shape at 1K magnification. [Figure 14] 1 shows SEM analysis results of the positive electrode active material of Example 2, (a) an image of particle shape at 25K magnification and (b) an image of particle shape at 1K magnification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0041] term In the present invention, the term "primary particle" refers to a particle unit in which no grain boundaries are apparent when observed at a magnification of 5,000 to 20,000 using a scanning electron microscope (SEM).
[0042] In the present invention, the term "secondary particles" refers to particles formed by agglomeration of a plurality of primary particles.
[0043] In the present invention, the term "average particle size (D 50 )" means the particle size at the 50% point of the volume cumulative distribution by particle size.
[0044] Measurement method In the present invention, the porosity of the precursor, the ratio of the area of the core to the total area of the precursor, and the porosity of the core were measured using images of particle cross sections using SEM and an image analysis program.
[0045] Specifically, a cross-sectional image (magnification 50K) of each precursor was obtained using a SEM (Hitachi), and the porosity, core porosity, and ratio of core area to total area of the precursor were analyzed. The precursor, conductive material, carbon black Super-P, and binder, poly(vinylidene fluoride) were used in a weight ratio of 54:4:43 (based on 1 g of precursor), and were uniformly mixed with 1.8 g of N-methylpyrrolidone to prepare a slurry. The prepared slurry was thinly applied to an aluminum foil with a thickness of 0.25 mm and dried at 100°C to prepare an electrode for cross-sectional measurement. An ion milling machine was used to irradiate the cross-section of the electrode to which the precursor was applied with an ion beam to prepare a test piece for SEM measurement. The SEM test piece was used to obtain a cross-sectional image of the precursor, and a particle was selected from the cross-sectional image. The cross-section of one particle was extracted using the watershed image processing technique with an image processing program (Pore analysis), and the core was separated using the erosion image processing technique. The image was then converted to binary using the threshold image processing technique, and the precursor porosity, core porosity, and ratio of the core area to the total area were analyzed. Here, the core was set to the part where pores were densely packed inside the particle, and the program was used to set the area formed by connecting the pores present at the outermost edge of the internal pores as the core. In addition, 10 particles with a particle diameter of 2 to 8 μm were selected from the cross-sectional image, and the precursor porosity, core porosity, and ratio of the core area to the total area were measured for each particle using the above method, and the results were expressed as the average value of these measured values.
[0046] In the present invention, the average particle size was measured using a particle size analyzer (S-3500, manufactured by Microtrac) with the particle size characteristics of the precursor set at a refractive index of 1.55.
[0047] In the present invention, the tap density was measured by putting 50 g of the precursor into a 50 ml measuring cylinder and performing 3000 strokes using a TAPDENSER (KYT-4000K, Seishin Enterprise Co., Ltd.).
[0048] In the present invention, the specific surface area was measured at a P / Po (relative pressure) of 0.05-0.2 after pretreating the precursor at 150° C. for 3 hours using a Tristar II 3020 (manufactured by Micromeritics).
[0049] The present invention provides a cathode active material precursor, a method for producing the same, a cathode active material containing a reaction product of the same and a lithium source material, and a method for producing a cathode active material using the cathode active material precursor.
[0050] The present invention will now be described in more detail.
[0051] Positive electrode active material precursor The present invention provides a positive electrode active material precursor that has a particle morphology in which a core portion has many voids and a shell portion is dense and has voids, thereby enabling improvement in charge / discharge capacity.
[0052] The positive electrode active material precursor according to one embodiment of the present invention includes secondary particles formed by agglomeration of a plurality of primary particles, which contain Ni and Mn, and the secondary particles have a ratio of a core area to a total area of the particle (core area / total area) of 28.7% to 34.1% and a porosity represented by the following mathematical formula 1 of 11.3% to 11.7%.
[0053] [Mathematical formula 1] Porosity (%) = (void area of whole particle / area of whole particle) x 100
[0054] In addition, the core porosity of the secondary particles may be 13.50% to 15.00%, and the average particle size (D 50 ) can be 3 μm to 15 μm.
[0055] The primary particles may be needle-shaped with a thickness of 40 nm to 100 nm and an aspect ratio of 3-10.
[0056] In another example, the positive electrode active material precursor may be represented by Formula 1 below.
[0057] [Chemical formula 1] [Ni a Mn b M 1 c ](OH)2
[0058] In the above Chemical Formula 1, 0 <a<0.4、0.5≦b<1、0≦c≦0.1であり、M 1 is one or more selected from the group consisting of Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Mo, Y, W and Zr.
[0059] The positive electrode active material precursor has a specific surface area of 20 m 2 / g~35m 2 / g, and the tap density can be 1.4 g / cc to 2.0 g / cc.
[0060] In another example, the positive electrode active material precursor has a specific surface area of 15 m 2 / g~30m 2 / g, and the tap density can be 1.4 g / cc to 2.0 g / cc.
[0061] In yet another example, the positive electrode active material precursor has an average particle size (D 50 ) is 3μm to 6μm, and the specific surface area is 20m 2 / g~35m 2 / g, and the tap density can be 1.4 g / cc to 2.0 g / cc.
[0062] In yet another example, the positive electrode active material precursor has an average particle size (D 50 ) is 7μm to 15μm, and the specific surface area is 15m 2 / g~30m 2 / g, and the tap density can be 1.4 g / cc to 2.0 g / cc.
[0063] Method for producing a positive electrode active material precursor The present invention provides a method for producing a positive electrode active material precursor, which can produce the positive electrode active material precursor with high reproducibility of physical properties in an environmentally friendly manner.
[0064] The method for preparing the cathode active material precursor according to an embodiment of the present invention includes a step of co-precipitating two or more transition metal source materials in the presence of a basic aqueous solution under a nitrogen atmosphere to prepare a reaction solution containing a transition metal hydroxide, and the co-precipitation reaction can be performed by introducing air in the absence of ammonia.
[0065] The coprecipitation reaction is carried out to produce a transition metal hydroxide from a transition metal raw material, and is carried out in a nitrogen atmosphere in the presence of a basic aqueous solution by introducing air, and can be carried out in the absence of ammonia. Here, the phrase "in the presence of a basic aqueous solution" means that the basic aqueous solution is included as a reactant during the coprecipitation reaction.
[0066] In general, the precursor of the NCM-based positive electrode active material is synthesized by forming a complex with a transition metal salt using ammonia, which is a complexing agent, but the ammonia is a malodorous and environmentally regulated substance, and the construction of a processing system is essential, and the cost of the processing system is excessive depending on the production scale, so there is a problem of poor process efficiency when applied to industry. In addition, ammonia plays a role of a catalyst in the synthesis of the precursor, and the physical properties of the precursor produced are greatly affected depending on its concentration, and it is difficult to adjust the primary particles and micropores of the precursor, so that when applied as a positive electrode active material, it is difficult to adjust the diffusion speed of Li, there are limitations in capacity and output characteristics, and it is difficult to reproduce constant physical properties of the positive electrode active material.
[0067] However, in the method for producing a positive electrode active material according to the present invention, the coprecipitation reaction is carried out in the absence of ammonia, and air is introduced under a nitrogen atmosphere, so that the air plays the role of ammonia instead, and therefore the coprecipitation reaction is carried out smoothly, and the method is environmentally friendly and has high reproducibility.
[0068] Specifically, the coprecipitation reaction according to one embodiment of the present invention may be carried out under a nitrogen atmosphere by introducing air, and the air may be introduced at more than 0 vol% and less than 10 vol%, more specifically, more than 0 vol% and 5 vol% or less, relative to 100 vol% of nitrogen.
[0069] More specifically, the coprecipitation reaction is carried out under a nitrogen atmosphere by continuously introducing air, and the total amount of air introduced during the coprecipitation reaction may be more than 0 volume% and less than 10 volume%, or more than 0 volume% and 5 volume% or less, based on the total amount of nitrogen used during the coprecipitation reaction (100 volume%). For example, when the air is introduced at 10 volume% or more based on the nitrogen, aggregation occurs between the produced precursor particles, which may require an additional grinding process, or the particle size and particle state may be deformed, making it difficult to produce a positive electrode active material precursor that satisfies the above physical properties.
[0070] The transition metal source material may be a sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide or oxyhydroxide of a transition metal, and the transition metal may be two or more selected from Ni, Mn, Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Mo, Y, W and Zr.
[0071] As another example, the transition metal source material may include a nickel source material and a manganese source material.
[0072] Specifically, the nickel source material may be, for example, nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and more specific examples thereof may be, but are not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salt, nickel halide, or a combination thereof.
[0073] In addition, the manganese source material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specific examples thereof include manganese oxides such as Mn2O3, MnO2, and Mn3O4; manganese salts such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid salt; manganese oxyhydroxide, manganese chloride, or combinations thereof, but are not limited thereto.
[0074] As yet another example, the metal solution may optionally contain 1 Contains raw materials and / or M 2 Ingredient materials may further be included.
[0075] Said M 1 In the raw material, M 1 The element may be one or more selected from the group consisting of Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Mo, Y, W and Zr, and M 1 The raw material contained is the above-mentioned M 1 The salt may be an acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide containing the element.
[0076] In addition, the transition metal source material may be used in the form of a metal solution in which the transition metal source material is dissolved in a solvent for a more uniform coprecipitation reaction. Here, the metal solution may be prepared by adding the transition metal source material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water, or by mixing an aqueous solution of the transition metal source material.
[0077] Here, the transition metal source materials can be mixed in a stoichiometric ratio that satisfies the molar ratio of each element in the transition metal hydroxide particles formed by the coprecipitation reaction. That is, in the present invention, the transition metal source materials can be mixed in an amount that satisfies the molar fractions of a, b, and c in [Chemical Formula 1] described below.
[0078] The basic aqueous solution may be prepared by dissolving a strong basic compound as a precipitant in distilled water.
[0079] The basic aqueous solution may contain 15 wt % to 35 wt % of a strong basic compound or have a pH of 9 to 13.
[0080] Here, the strong base compound can be an alkali metal hydroxide or hydrate, an alkaline earth metal hydroxide or hydrate, or a combination thereof, and more specifically, the strong base compound can be sodium hydroxide, potassium hydroxide, calcium hydroxide, lithium hydroxide, or a combination thereof.
[0081] As another example, the basic aqueous solution may be at least one selected from the group consisting of an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous calcium hydroxide solution, and an aqueous lithium hydroxide solution.
[0082] The basic aqueous solution is added during the coprecipitation reaction to adjust the pH, and may be added in an amount that provides a pH of 9 to 13 in the reaction system in which the coprecipitation reaction is carried out.
[0083] Meanwhile, the coprecipitation reaction may be carried out at a temperature of 40° C. to 70° C. In order to increase the reaction rate of the coprecipitation reaction, a stirring process may be optionally carried out, and the stirring speed may be 100 rpm to 2000 rpm.
[0084] As another example, the method for producing the positive electrode active material precursor according to an embodiment of the present invention may further include a step of aging the reaction solution after the co-precipitation reaction, and the aging may be performed by leaving the reaction solution to stand under a nitrogen atmosphere and a condition of pH 12 to 14 for 6 to 24 hours.
[0085] As another example, the aging can be carried out in a temperature range of 30°C to 50°C.
[0086] The NCM-based positive electrode active material precursor used in the manufacture of lithium-rich NCM-based positive electrode active material is synthesized by a coprecipitation method, and recently, methods for improving the density of the precursor have been studied in order to maximize the energy density of the battery, and one of these methods is the coprecipitation method in the presence of a basic solution (e.g., sodium hydroxide). In this case, metal oxides (e.g., manganese oxides) are generated in the reaction system in addition to the target precursor material, which causes aggregation of precursor particles when dried after washing, causing problems in the classification process, and even after being used as a positive electrode active material raw material and sintered, they remain as impurities in the positive electrode active material, causing a decrease in the capacity and life of the positive electrode active material.
[0087] In the method for producing a cathode active material precursor according to the present invention, when the aging step is further included after the co-precipitation reaction, oxidation of transition metal hydroxide in the reaction solution is prevented and generation of metal oxide, particularly manganese oxide, is suppressed, thereby eliminating problems in the aggregation and classification process caused by the metal oxide during drying, and the finally produced cathode active material precursor has the effect of being free of metal oxide impurities or having a significantly reduced amount of impurities compared to the conventional method.
[0088] As yet another example, in the manufacturing method according to one embodiment of the present invention, the aging can be carried out for 12 to 24 hours under a nitrogen atmosphere, at a pH of 13 to 14 and at a temperature of 40°C to 50°C, in order to more easily achieve the intended effect.
[0089] On the other hand, in the aging step, the pH condition can be determined by adding a strong base compound to the reaction solution, and the strong base compound can be added as it is or in the form of an aqueous solution obtained by dissolving it in distilled water. The strong base compound is not particularly limited as long as it is generally known as a strong base compound, and can be, for example, sodium hydroxide, potassium hydroxide, calcium hydroxide, or lithium hydroxide.
[0090] As yet another example, a method for producing a positive electrode active material precursor according to an embodiment of the present invention may include the steps of co-precipitating two or more transition metal source materials in the presence of a basic aqueous solution under a nitrogen atmosphere to produce a reaction solution containing a transition metal hydroxide, aging the reaction solution, and sequentially performing washing, filtering, and drying.
[0091] Here, the co-precipitation and aging steps are as described above, and the washing, filtering and drying steps can be carried out by means commonly used in the art.
[0092] The washing may be performed in the order of a primary washing and a secondary washing, the primary washing being performed using a basic aqueous solution, and the secondary washing being performed using distilled water.
[0093] Here, the basic aqueous solution used in the primary washing may have a pH of 12 to 14, and for example, the basic aqueous solution may contain 2 wt % to 5 wt % of a strong basic compound.
[0094] In the method for preparing a cathode active material precursor according to the present invention, when the washing is performed by first washing with a basic aqueous solution and then second washing with distilled water, oxidation of the transition metal hydroxide that may occur during the washing process can be prevented and impurities can be further removed.
[0095] The drying can be carried out at 110° C. to 400° C. for 15 to 30 hours.
[0096] positive electrode active material The present invention provides a positive electrode active material comprising a lithium transition metal oxide, which is a reaction product of the positive electrode active material precursor and a lithium source material.
[0097] The cathode active material according to an embodiment of the present invention includes a lithium transition metal oxide that is a reaction product of the cathode active material precursor and a lithium raw material, and includes secondary particles formed by agglomeration of a plurality of primary particles, and the secondary particles have a shell thickness ratio of 30% to 60% relative to the semi-major axis of the particle.
[0098] In another example, the positive electrode active material may be represented by Formula 2 below.
[0099] [Chemical formula 2] Li x [Ni a Mn b M 1 c ]O2
[0100] In the above Chemical Formula 2, 1.1 <a<1.3、0<a<0.4、0.5≦b<1、0≦c≦0.1、x+a+b+c=2であり、M 1 is one or more selected from the group consisting of Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Mo, Y, W and Zr.
[0101] Method for producing positive electrode active material The present invention provides a method for producing the positive electrode active material using the positive electrode active material precursor.
[0102] A method for preparing a positive electrode active material according to an embodiment of the present invention may include mixing the positive electrode active material precursor and a lithium source material, and calcining the mixture.
[0103] Specifically, the method for producing a positive electrode active material according to the present invention can be carried out by a method for producing a positive electrode active material well known in the art, except for using the positive electrode active material precursor according to the present invention, and the method is not particularly limited.
[0104] The lithium source material may be a lithium-containing carbonate (e.g., lithium carbonate, etc.), a hydrate (e.g., lithium hydroxide hydrate (LiOH·H2O), etc.), a hydroxide (e.g., lithium hydroxide), a nitrate (e.g., lithium nitrate (LiNO3), etc.), a chloride (e.g., lithium chloride (LiCl), etc.), etc., and one or more of these may be used alone or in combination.
[0105] Meanwhile, the mixing of the positive electrode active material precursor and the lithium source material may be performed by solid-phase mixing such as jet milling, and the mixing ratio of the positive electrode active material precursor and the lithium source material may be determined within a range that satisfies the molar fraction of each component in the finally manufactured positive electrode active material. More specifically, the positive electrode active material precursor and the lithium source material may be mixed such that the molar ratio of lithium element in the positive electrode active material precursor and the lithium source material is 1:1.2 to 1:1.6.
[0106] In addition, although not essential, a source material for doping a part of the transition metal and / or oxygen of the positive electrode active material may be further included in addition to the positive electrode active material precursor and the lithium source material during the mixing. For example, the above-mentioned M 1The X-containing raw material may further be mixed with the X-containing raw material described later. Here, the X-containing raw material may be, for example, Na3PO4, K3PO4, Mg3(PO4)2, AlF3, NH4F, LiF, etc., but is not limited thereto. As described above, when a part of oxygen is replaced by the X element, it is possible to obtain an effect of suppressing the release of oxygen and the reaction with the electrolyte during charging and discharging of the secondary battery.
[0107] Meanwhile, the firing may be performed at 700°C to 900°C, specifically 750°C to 850°C, and the firing time may be 5 hours to 30 hours, specifically 8 hours to 15 hours, but is not limited thereto.
[0108] Meanwhile, after the calcination, a water washing step and a drying step may be further performed to remove lithium by-products. The water washing step may be performed, for example, by putting the prepared positive electrode active material into ultrapure water and stirring the mixture. Here, the water washing temperature may be 20° C. or less, specifically, 10° C. to 20° C., and the water washing time may be about 10 minutes to 1 hour. When the water washing temperature and water washing time satisfy the above ranges, the lithium by-products may be effectively removed.
[0109] Positive Electrode and Secondary Battery The positive electrode active material prepared by the method for preparing a positive electrode active material according to the present invention can be usefully used in the manufacture of a positive electrode for a secondary battery.
[0110] Specifically, the positive electrode for a secondary battery according to the present invention includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, where the positive electrode active material layer includes the positive electrode active material.
[0111] The positive electrode may be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode active material. For example, the positive electrode may be manufactured by dissolving or dispersing the components constituting the positive electrode active material layer, i.e., the positive electrode active material, a conductive material and / or a binder, in a solvent to manufacture a positive electrode mixture, applying the positive electrode mixture to at least one surface of a positive electrode current collector, and then drying and rolling the mixture, or by casting the positive electrode mixture on another support, peeling it off from the support, and laminating the film obtained on the positive electrode current collector.
[0112] Here, the positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0113] A positive electrode active material layer including the positive electrode active material according to the present invention and, if necessary, selectively including at least one of a conductive material and a binder is located on at least one surface of the current collector.
[0114] The positive electrode active material may be contained in an amount of 80 to 99 wt %, more specifically, 85 to 98 wt %, based on the total weight of the positive electrode active material layer. When contained in the above content range, excellent capacity characteristics can be exhibited.
[0115] The conductive material is used to give the electrode conductivity, and can be used without any particular limitation as long as it does not cause a chemical change in the battery to be constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be contained in an amount of 1% by weight to 30% by weight based on the total weight of the positive electrode active material layer.
[0116] The binder also serves to improve adhesion between the positive electrode active material particles and adhesion between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer.
[0117] Meanwhile, the solvent used in the preparation of the positive electrode composite may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., which may be used alone or in combination. The amount of the solvent used may be appropriately adjusted in consideration of the coating thickness, production yield, viscosity, etc. of the slurry.
[0118] In addition, the secondary battery according to the present invention includes a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the positive electrode according to the present invention described above.
[0119] Meanwhile, the secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0120] In the secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector.
[0121] The negative electrode may be manufactured by a conventional method for manufacturing a negative electrode that is generally known in the art. For example, the negative electrode may be manufactured by dissolving or dispersing the components constituting the negative electrode active material layer, i.e., the negative electrode active material, a conductive material, and / or a binder, in a solvent to manufacture a negative electrode mixture, applying the negative electrode mixture to at least one surface of a negative electrode current collector, and then drying and rolling the negative electrode mixture, or by casting the negative electrode mixture on another support, peeling it off from the support, and laminating the resulting film on the negative electrode current collector.
[0122] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0123] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO v(0 < v < 2), metal oxides such as SnO2, vanadium oxides, and lithium vanadium oxides that can be doped and undoped with lithium; or composites containing the metallic compound and a carbonaceous material such as Si-C composites or Sn-C composites, etc. may be mentioned, and any one or a mixture of two or more of these can be used. Further, a thin film of metallic lithium can also be used as the negative electrode active material. Also, as the carbon material, both low-crystalline carbon and high-crystalline carbon can be used. Representative examples of low-crystalline carbon are soft carbon and hard carbon, and representative examples of high-crystalline carbon are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch derived cokes.
[0124] Further, the binder and the conductive material are as described above for the positive electrode.
[0125] Meanwhile, in the secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc. can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single layer or multilayer structure.
[0126] On the other hand, examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used when manufacturing a secondary battery, but are not limited to these.
[0127] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0128] The organic solvent can be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; an ether solvent such as dibutyl ether or tetrahydrofuran, etc.; a ketone solvent such as cyclohexanone, etc.; an aromatic hydrocarbon solvent such as benzene or fluorobenzene, etc.; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), propylene carbonate (propylene carbonate), etc. Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethanol and isopropyl alcohol, nitriles such as Ra-CN (Ra is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9 to provide excellent electrolyte performance.
[0129] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within a range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance, and lithium ions can move effectively.
[0130] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, or pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.
[0131] As described above, the secondary battery including the positive electrode active material according to the present invention has excellent capacity characteristics and high temperature stability, and can be usefully applied to portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0132] In addition, the secondary battery according to the present invention may be used as a unit cell of a battery module, and the battery module may be applied to a battery pack. The battery module or the battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (EV), a hybrid electric vehicle, and an electric plug-in hybrid electric vehicle (PHEV), or a power storage system.
[0133] Working Example DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.
[0134] Experimental Material I Example 1 Nickel sulfate and manganese sulfate were dissolved in ion-exchanged water so that the molar ratio of nickel to manganese was 0.35:0.65 to prepare a 2.4 M metal solution, and a 25% aqueous solution of sodium hydroxide was separately prepared.
[0135] Nitrogen gas was introduced into a coprecipitation reactor set at 50° C. at 300 L / hr to create a nitrogen atmosphere, and the metal solution and sodium hydroxide aqueous solution were introduced at rates of 0.5 L / hr and 0.3 L / hr, respectively, to carry out the coprecipitation reaction for 24 hours. Here, the coprecipitation reaction was carried out while introducing air at 15 L / hr (5% by volume relative to 100% by volume of nitrogen).
[0136] Thereafter, the mixture was washed with water, filtered, and then dried at 120° C. for 12 hours to prepare a positive electrode active material precursor.
[0137] Comparative Example 1 Nickel sulfate and manganese sulfate were dissolved in ion-exchanged water so that the molar ratio of nickel to manganese was 0.35:0.65 to prepare a 2.4 M metal solution, and separately, a 25% aqueous solution of sodium hydroxide was prepared.
[0138] Nitrogen gas was fed into a coprecipitation reactor set at 50°C at 300 L / hr to create a nitrogen atmosphere, and the metal solution, sodium hydroxide aqueous solution, and 9% ammonia aqueous solution were fed at rates of 0.5 L / hr, 0.3 L / hr, and 0.12 L / hr to carry out the coprecipitation reaction.
[0139] Then, the mixture was washed with water, filtered, and dried at 120° C. for 12 hours to prepare a positive electrode active material precursor.
[0140] Comparative Example 2 A positive electrode active material precursor was produced in the same manner as in Example 1, except that the coprecipitation reaction was carried out while introducing 10% by volume of air relative to 100% by volume of nitrogen.
[0141] Comparative Example 3 A positive electrode active material precursor was produced in the same manner as in Example 1, except that the coprecipitation reaction was carried out while introducing 50 volume % of air with respect to 100 volume % of nitrogen.
[0142] Comparative Example 4 A positive electrode active material precursor was produced in the same manner as in Example 1, except that the coprecipitation reaction was carried out while introducing 100% by volume of air instead of introducing nitrogen during the coprecipitation reaction.
[0143] Experimental Example 1 The particle characteristics of the positive electrode active material precursors prepared in the examples and comparative examples were compared and analyzed.
[0144] (1) SEM measurement The particle shape of each precursor was confirmed using an SEM (Hitachi Corporation), and the results are shown in FIGS.
[0145] (2) Particle size analysis The particle size characteristics of each precursor were measured using a particle size analyzer (S-3500, manufactured by Microtrac) with the refractive index set to 1.55. The diameter (D 50 ), 5% diameter (D5), 95% diameter (D 95 ), maximum diameter (D max ), minimum diameter (D min ) was calculated, and the results are shown in Table 1 below and FIG.
[0146] (3) Tap density analysis 50 g of each precursor was placed in a 50 ml graduated cylinder, and the tap density was measured by 3000 strokes using a TAPDENSER (KYT-4000K, Seishin Enterprise Co., Ltd.). The results are shown in Table 1 below.
[0147] (4) Specific surface area Each precursor was pretreated at 150° C. for 3 hours using a Tristar II 3020 (Micromeritics), and then the specific surface area was measured at a P / Po (relative pressure) of 0.05-0.2. The results are shown in Table 1 below.
[0148] (5) Particle structure analysis Cross-sectional images (magnification: 50K) of each precursor were obtained using a SEM (Hitachi), and the porosity, core porosity, and ratio of the core area to the total area of the precursor were analyzed.
[0149] Each precursor, carbon black Super-P as a conductive material, and poly(vinylidene fluoride) as a binder were used in a weight ratio of 54:4:43 (based on 1 g of precursor), and were uniformly mixed with 1.8 g of N-methylpyrrolidone to prepare a slurry. The prepared slurry was thinly applied to an aluminum foil with a thickness of 0.25 mm and dried at 100°C to prepare an electrode for cross-section measurement. An ion beam was irradiated to the cross-section of the electrode coated with the precursor using an ion milling device to prepare a test piece for SEM measurement.
[0150] Then, images of each cross section were obtained from the test specimen using SEM, particles were selected from the cross section images, and the cross section of one particle was extracted using the watershed image processing technique with an image processing program (Pore analysis), and the core was identified using the erosion image processing technique. The image was then converted to binary using the threshold image processing technique, and the precursor porosity, core porosity, and ratio of core area to total area were analyzed. Here, the core was set as the part where pores were densely packed inside the particle, and the program was used to set the area formed by connecting the pores at the outermost edge of the internal pores as the core.
[0151] In addition, 10 particles with diameters of 2 to 8 μm were selected from each cross-sectional image, and the precursor porosity, core porosity, and ratio of core area to total area were measured for each particle using the above-mentioned method, and the results were expressed as the average values of these measurements.
[0152] [Table 1]
[0153] As shown in Table 1, it was confirmed that the positive electrode active material precursor of Example 1 had similar particle size characteristics and tap density to the positive electrode active material precursor of Comparative Example 1. In addition, the positive electrode active material precursor of Example 1 had a similar overall porosity to the positive electrode active material precursor of Comparative Example 1, but had a low core area ratio and a high core porosity, satisfying the porosity and core area ratio proposed in the present invention.
[0154] In addition, it was confirmed that the positive electrode active material precursor of Example 1 exhibits particle characteristics in which the core has many voids and the shell (outside) is dense with fine voids, whereas the positive electrode active material precursor of Comparative Example 1 has voids only in the core and a thick shell (see FIG. 2(b) and FIG. 4(b)).
[0155] In addition, in the case of the positive electrode active material precursor of Comparative Example 2, the tap density was significantly reduced compared to Example 1 and Comparative Example 1, and the particles had many voids throughout the entire inside and outside of the particles, exhibiting particle characteristics in which the core and shell were not separated (see FIG. 5(b)).
[0156] Experimental Example 2 Positive electrode active materials were produced using the positive electrode active material precursors produced in the examples and comparative examples, and the particle characteristics of the positive electrode active materials were compared and analyzed.
[0157] Each positive electrode active material precursor was mixed with LiOH so that the transition metals (Ni and Mn) in the precursor and Li in the LiOH were in a molar ratio of 1:1.35, and then calcined at 700° C. for 15 hours in an air atmosphere to produce each positive electrode active material.
[0158] The particle shape of each of the produced positive electrode active materials was confirmed at a magnification of 50K using an SEM (manufactured by Hitachi Corporation), and the results are shown in FIGS.
[0159] In addition, the ratio of shell thickness to particle radius of the positive electrode active material was analyzed, and the results are shown in Table 2 below.
[0160] The ratio of the shell thickness to the particle semimajor axis was calculated by preparing an electrode for cross-section measurement in the same manner as in Experimental Example 1, except that an active material was used instead of the precursor, and then preparing a test piece for SEM measurement. An image of the cross section at a magnification of 50K was obtained by SEM, measuring the semimajor axis of the particle, and using the distance from the outer edge of the core to the outer surface of the particle on the semimajor axis as the shell thickness, [shell thickness / semimajor axis of particle] x 100. Here, the outer edge of the core was determined by regarding the part where pores are densely packed inside the particle as the core, and the pores present at the outermost edge of the internal pores as the boundary between the core and the shell, and the core outer edge. In addition, 10 particles with a particle diameter of 2 to 8 μm were selected from each cross-sectional image, and the ratio of the shell thickness to the particle semimajor axis was calculated for each particle by the above method, and the results were shown as the average value of these values.
[0161] [Table 2]
[0162] As shown in Table 2, it was confirmed that the positive electrode active material of Example 1 satisfied the range of the ratio of the shell thickness to the semi-major axis of the particle.
[0163] Experimental Example 3 A positive electrode active material was produced using each of the positive electrode active material precursors produced in the Examples and Comparative Examples, and a battery was produced using the positive electrode active material, after which the battery performance was evaluated.
[0164] (1) Manufacturing of positive electrode active material Each positive electrode active material precursor and LiOH were mixed so that the transition metals (Ni and Mn) in the precursor and Li in the LiOH were in a molar ratio of 1:1.35, and then calcined at 700° C. for 15 hours in an air atmosphere to produce each positive electrode active material.
[0165] (2) Manufacturing of positive electrodes The prepared positive electrode active materials, carbon black conductive material, and PVdF binder were mixed in a weight ratio of 96.5:1.5:2.0 in N-methylpyrrolidone solvent to prepare a positive electrode mixture (viscosity: 5000 mPa S). The positive electrode mixture was applied to one side of an aluminum current collector, dried at 130°C, and rolled to prepare a positive electrode.
[0166] (3) Battery manufacturing The negative electrode used was lithium metal. A porous polyethylene separator was interposed between the positive and negative electrodes to prepare an electrode assembly, and the electrode assembly was placed inside a case, and an electrolyte was injected into the case to prepare a lithium secondary battery. The electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1.0 M in an organic solvent consisting of ethylene carbonate / diethyl carbonate / ethyl methyl carbonate (EC / DEC / EMC mixed volume ratio = 3 / 2 / 5).
[0167] Each lithium secondary battery half cell prepared as above was charged at 0.33 C in CCCV mode at 25° C. to 4.4 V, and discharged at a constant current of 0.33 C to 2.5 V to measure the initial charge / discharge capacity and efficiency. The results are shown in Table 3 below.
[0168] [Table 3]
[0169] It can be seen from Table 3 that the positive electrode active material of Example 1 is superior to the positive electrode active materials of Comparative Examples 1 and 2 in initial charge / discharge capacity and efficiency.
[0170] Experimental Data II Example 2 A coprecipitation reaction was carried out in the same manner as in Example 1 to prepare a reaction solution.
[0171] Thereafter, the reaction solution was aged at 50° C. for 6 hours under a nitrogen atmosphere at a pH of 13. The reaction solution was then washed with water, filtered, and dried at 120° C. for 12 hours to prepare a positive electrode active material precursor.
[0172] Example 3 A positive electrode active material precursor was produced in the same manner as in Example 2, except that after aging, the washing step was performed by first washing with a 2 wt % sodium hydroxide aqueous solution and then second washing with distilled water.
[0173] Experimental Example 4 The particle characteristics of the positive electrode active material precursors of Examples 2 and 3 were analyzed.
[0174] (1) SEM measurement The particle shape of each precursor was confirmed by analysis at magnifications of 1K and 15K using an SEM (Hitachi Corporation), and the results are shown in FIGS.
[0175] (2)XRD measurement The crystallinity of each precursor was analyzed using an XRD (Rigaku) with a start angle of 10°, an end angle of 70°, and a scan speed of 4° / min. The results are shown in FIG.
[0176] (3) Particle size analysis The particle size characteristics of each precursor were measured using a particle size analyzer (S-3500, manufactured by Microtrac) with the refractive index set to 1.55. The diameter (D 50 ), 5% diameter (D5), 95% diameter (D 95 ), maximum diameter (D max ), minimum diameter (D min ) was calculated, and the results are shown in Table 4 below.
[0177] (4) Tap density analysis 50 g of each precursor was placed in a 50 ml measuring cylinder, and the tap density was measured by performing 3000 strokes using a TAPDENSER (KYT-4000K, Seishin Enterprise Co., Ltd.). The results are shown in Table 4 below.
[0178] (5) Specific surface area Each precursor was pretreated at 150° C. for 3 hours using a Tristar II 3020 (Micromeritics), and then the specific surface area was measured at a P / Po (relative pressure) of 0.05-0.2. The results are shown in Table 4 below.
[0179] (6) Classification rate (%) The classification rate is the actual amount of each precursor obtained after drying, and was calculated by the following mathematical formula 2.
[0180] [Mathematical formula 2] Classification rate (%) = [Weight of precursor after classification (kg) / Weight of precursor before classification (kg)] × 100
[0181] [Table 4]
[0182] 10 and 11, it was confirmed that the positive electrode active material precursors of Examples 2 and 3 exhibited particle shapes similar to those of the positive electrode active material precursor of Example 1, and had excellent classification rates, lower specific surface areas, and higher tap densities. In addition, referring to FIG. 12, it was confirmed that no manganese oxide (Mn3O4) peaks were observed in the positive electrode active material precursors produced in Examples 2 and 3.
[0183] The above results indicate that, in the case of the cathode active material precursor of the present invention, when it is prepared by a preparation method further including an aging step and a washing step, the characteristics of the precursor particles are not changed, and oxidation of the transition metal hydroxide is prevented to suppress the generation of metal oxide, thereby eliminating the problems of aggregation and classification during drying, resulting in a significantly excellent classification rate and the absence or significant reduction of impurities in the precursor.
[0184] Experimental Example 5 Positive electrode active materials were produced using the positive electrode active material precursors produced in Examples 2 and 3, and batteries were produced using the positive electrode active materials. The battery performance was then evaluated. The results are shown in Table 5.
[0185] Here, the preparation of the positive electrode active material and the initial charge / discharge capacity and initial efficiency were performed in the same manner as in Experimental Example 3. In addition, the capacity retention rate was confirmed after measuring at C-rate and repeating charging at 0.1 C and discharging at 0.1 C 30 times.
[0186] In addition, each of the produced positive electrode active materials was analyzed using an SEM (manufactured by Hitachi) at magnifications of 1K and 25K to confirm the particle shape of each precursor, and the results are shown in FIGS.
[0187] [Table 5]
[0188] It was confirmed from Table 5 that the positive electrode active materials of Examples 2 and 3 were superior to the positive electrode active material of Example 1 in charge / discharge capacity.
Claims
1. Contains Ni and Mn, The secondary particles are formed by agglomeration of a plurality of primary particles, The secondary particles have a ratio of a core area to a total area of the particle (core area / total area) of 28.7% to 34.1%, and a porosity represented by the following mathematical formula 1 of 11.3% to 11.7%. [Mathematical formula 1] Porosity (%)=(void area of whole particle / area of whole particle)×100
2. 2. The positive electrode active material precursor according to claim 1, wherein the secondary particles have a core porosity of 13.5% to 15.0%.
3. The average particle diameter of the secondary particles (D 50 2. The positive electrode active material precursor according to claim 1, wherein the average particle diameter is 3 μm to 15 μm.
4. 2. The cathode active material precursor of claim 1, wherein the primary particles are acicular with a thickness of 40 nm to 100 nm and an aspect ratio of 3 to 10.
5. The positive electrode active material precursor according to claim 1 , represented by the following chemical formula 1: [Chemical formula 1] [Ni a Mn b M 1 c ](OH) 2 In the above formula 1, 0<a<0.4, 0.5≦b<1, and 0≦c≦0.1; M 1 is one or more selected from the group consisting of Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Mo, Y, W and Zr.
6. Specific surface area is 20m 2 / g to 35m 2 / g and a tap density of 1.4 g / cc to 2.0 g / cc.
7. Specific surface area is 15m 2 / g to 30m 2 / g and a tap density of 1.4 g / cc to 2.0 g / cc.
8. The method includes a step of co-precipitating two or more transition metal source materials in the presence of a basic aqueous solution under a nitrogen atmosphere to produce a reaction solution containing a transition metal hydroxide, The coprecipitation reaction is carried out in the absence of ammonia by introducing air.
9. The method for producing a positive electrode active material precursor according to claim 8 , wherein the air is introduced in an amount of more than 0 vol % and less than 10 vol % with respect to 100 vol % of nitrogen.
10. The coprecipitation reaction is carried out by continuously introducing air, 9. The method for producing a cathode active material precursor according to claim 8, wherein a total amount of air introduced during the coprecipitation reaction is more than 0 vol% and 5 vol% or less with respect to 100 vol% of a total amount of nitrogen used during the coprecipitation reaction.
11. The method further comprises a step of aging the reaction solution, 9. The method for producing a positive electrode active material precursor according to claim 8, wherein the aging is performed by leaving the reaction solution to stand in a nitrogen atmosphere at a pH of 12 to 14 for 6 to 24 hours.
12. The method for producing a positive electrode active material precursor according to claim 8, wherein the aging is carried out at a temperature in the range of 30°C to 50°C.
13. A step of co-precipitating two or more transition metal source materials in the presence of a basic aqueous solution under a nitrogen atmosphere to produce a reaction solution containing a transition metal hydroxide; Aging the reaction solution; and sequentially carrying out washing, filtering and drying.
14. The cleaning is performed in the order of a primary cleaning and a secondary cleaning, The method for producing a positive electrode active material precursor according to claim 13 , wherein the primary cleaning is performed using a basic aqueous solution, and the secondary cleaning is performed using distilled water.
15. 9. The method for producing a positive electrode active material precursor according to claim 8, wherein the transition metal is two or more selected from Ni, Co, Mn, Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Y, Mo, W, and Zr.
16. The positive electrode active material precursor according to claim 1 includes a lithium transition metal oxide that is a reaction product of the positive electrode active material precursor and a lithium source material, The secondary particles are formed by agglomeration of a plurality of primary particles, The secondary particles have a shell thickness ratio to the semi-major axis of the particle of 30% to 60%.
17. The positive electrode active material according to claim 16 , represented by the following chemical formula 2: [Chemical formula 2] Li x [Ni a Mn b M 1 c ]O 2 In the above formula 2, 1.1<a<1.3, 0<a<0.4, 0.5≦b<1, 0≦c≦0.1, and x+a+b+c=2; M 1 is one or more selected from the group consisting of Cu, Fe, Mg, B, Cr, V, Ti, Ta, Nb, Mo, Y, W and Zr.
18. Mixing the positive electrode active material precursor of claim 1 with a lithium source material; and baking the resulting mixture.
19. The method for producing a positive electrode active material according to claim 18, wherein the positive electrode active material precursor and the lithium source material are mixed such that a molar ratio of lithium element in the positive electrode active material precursor and the lithium source material is 1:1.2 to 1:1.6.
Citation Information
Patent Citations
Method for manufacturing positive electrode active material
CN113841269A
A core-shell structured lithium-rich manganese-based cathode material precursor and its preparation method
CN115140782B
Monocrystal positive electrode material precursor and preparation method and application thereof
CN116730405A
Nickel cobalt complex hydroxide particle and manufacturing method thereof, positive electrode active material for nonaqueous electrolyte secondary batteries and manufacturing method thereof, and nonaqueous electrolyte secondary battery
JP2015164123A
Nickel-based active material precursor for lithium secondary battery, method for producing the same, nickel-based active material formed therefrom for lithium secondary battery, and lithium secondary battery including positive electrode including the same
JP2020064858A